The Church in the Camouflage of Mass Housing Construction. The Ecumenical Centre of Scharnhorst-Ost in Dortmund - Anna Kloke (Histories of Postwar Architecture)
Located in the densely populated industrial region of western Germany, the Scharnhorst-Ost Ecumenical Centre is an example of the important social and urban function of parish centres, especially in the newly built social housing estates of the post-war period. Like many of the church buildings erected after the Second Vatican Council and influential Protestant Church Building Conferences such as that in Darmstadt in 1969, Scharnhorst, deliberately eschewed a traditional church building scheme as an expression of the desire for reform. They also decided to build two neighbouring churches as an ecumenical centre, which opened in 1974 after three years of construction. As the focus was to be on diaconal work, great importance was attached to the suitability of the parish centre's architecture for everyday use. The aim was to contribute to the development of social structures in the estate through interfaith life support and a wide range of educational and leisure activities. The new pastoral concept was also to be reflected in the architecture, which was to be designed as an open, low-threshold meeting place for everyone, and also to blend in with the urban context through deliberate simplicity. The Scharnhorst ecumenical community centre is part of a dense network of church buildings in the region, many of which are currently under threat of demolition or closure. Especially in cases such as Scharnhorst, where the conceptual qualities outweigh the directly perceived aesthetic or spiritual qualities, the public communication of the conceptual strengths is important both for the protection of this historical heritage of the region, for the preservation of its urban function, and for the preservation of the socially integrative communities located here.